A Class III asymmetric binuclear cyanido-bridged mixed-valence complex. (7th April 2022) - Liu, Xiao-Lin; Li, Yi; Xu, Qing-Dou; Wei, Zi-Qin; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : Asymmetric binuclear cyanido-bridged complexes, [Cp*(dppe)Ru II –CN–Ru II (bpy)2 Cl] + (1 + ), and their one-electron oxidized complexes 1 2+ have been synthesized and characterized. The investigations show that 1 2+ may be a Class III mixed-valence complex. Abstract : In this work, we report a pair of asymmetric cyanido-bridged binuclear Ru–CN–Ru–Cl complexes, [Cp*(dppe)Ru II –CN–Ru II/III (bpy)2 Cl] n + [BF4 ] n (1 n + [BF4 ] n, n = 1, 2; Cp* = 1, 2, 3, 4, 5-pentamethylcyclopentadiene, dppe = 1, 2-bis(diphenylphosphino)ethane, bpy = 2, 2′-bipyridine), and 1 2+ with Ru II –CN–Ru III is the one-electron oxidized product of 1 + with Ru II –CN–Ru II . Both the complexes are well characterized. The investigations indicate that 1 2+ is a completely delocalized (Class III) mixed-valence complex, confirmed by theoretical calculations. To the best our knowledge, 1 2+ is the first example of the structurally characterized asymmetric cyanido-bridged Class III mixed-valence complex.